Contextual Academic Supervision Management to Improve the Pedagogical Competence of Elementary School Teachers (Case Study at Kurniajaya Public Elementary School and Buniasih Public Elementary School, Tasikmalaya Regency) - Sutrisna, Sana; Rostini, Deti (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2025)
Abstract: The low utilization of contextual academic supervision in improving teachers' pedagogical competence remains a significant concern in elementary schools. This study aims to describe the planning, organization, implementation, supervision, obstacles, and solutions in the management of contextual academic supervision in Kurniajaya State Elementary School and Buniasih State Elementary School, Tasikmalaya Regency. This study was conducted for two weeks using a qualitative approach, taking the theory from G.R Terry through observation, in-depth interviews, and documentation studies. The results of the study indicate that contextual academic supervision in both schools has been implemented based on management principles, which include: (a) planning includes setting goals, identifying resources, strategies, and preparing schedules and budgets; (b) organizing is carried out through the formation of clear structures, delegation of tasks according to competencies, and strengthening teamwork; (c) implementation includes teacher mentoring, analysis of Education Reports, utilization of the GTK Space Platform, and learning reflection; and (d) supervision is carried out in a reflective-participatory manner by producing a continuous improvement plan. In addition, the study also found (e) obstacles in the form of limited time, differences in teacher commitment, and less than optimal utilization of digital facilities; and (f) solutions achieved through strengthening shared commitment, more flexible scheduling, and maximizing the use of simple technology. Thus, it can be concluded that contextual academic supervision management in both schools has been effective, although it still faces obstacles that need to be overcome with adaptive strategies to sustainably improve teachers' pedagogical competence. Keywords: academic supervision, contextual approach, teacher pedagogical competence, elementary school